New Developments in Microbiome in Alcohol-Associated and Nonalcoholic Fatty Liver Disease - Hartmann, Phillipp; Schnabl, Bernd (Seminars in Liver Disease, 2021)
Alcohol-associated liver disease (ALD) and nonalcoholic fatty liver disease (NAFLD) are important causes of morbidity and mortality worldwide. The intestinal microbiota is involved in the development and progression of both ALD and NAFLD. Here we describe associated changes in the intestinal microbiota, and we detail randomized clinical trials in ALD and NAFLD which evaluate treatments modulating the intestinal microbiome including fecal microbiota transplantation, probiotics, prebiotics, synbiotics, and antibiotics. Finally, we discuss precision medicine approaches targeting the intestinal microbiome to ameliorate ALD and NAFLD.
Keywords: microbiome; alcohol-associated liver disease; nonalcoholic fatty liver disease; new developments; precision medicine